A study of the gifts of the Spirit in relation to the fruit of the Spirit and the body of Christ in Pauline theology - Palmer, Roger Gordon (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--Stellenbosch University, 1985.